2018
DOI: 10.1101/431494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conservation of the structural and functional architecture of encapsulated ferritins in bacteria and archaea

Abstract: +44(0)191 208 4855, Jon.marles-wright1@ncl.ac.uk; David J. Clarke, +44(0)131 650 4808, Dave.clarke@ed.ac.uk. ABSTRACT Iron is an essential element for many biological processes; however, due to its high reactivity iron can also be very toxic, producing reactive oxygen species through Fenton chemistry. Ferritins protect the cell from oxidative stress by catalytically converting Fe(II) into less toxic Fe(III) and storing the resulting iron minerals within their core. Encapsulated ferritins (EncFtn) are a sub-fam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…The E34A variant had significantly more protein in the 82 ml peak when compared to the EncFtn-WT and E31A variant, suggesting that this change affects the stability of the protein complex. Based on our prior work, these peaks correspond to decamer, tetramer, and dimer species, respectively (14,24).…”
Section: Changes To the Metal Ion Entry Site Of Encapsulated Ferritinmentioning
confidence: 88%
See 4 more Smart Citations
“…The E34A variant had significantly more protein in the 82 ml peak when compared to the EncFtn-WT and E31A variant, suggesting that this change affects the stability of the protein complex. Based on our prior work, these peaks correspond to decamer, tetramer, and dimer species, respectively (14,24).…”
Section: Changes To the Metal Ion Entry Site Of Encapsulated Ferritinmentioning
confidence: 88%
“…To interrogate the stability and oligomeric states of the EncFtn variants, we performed native MS and ion mobility MS experiments on samples purified by size-exclusion chromatography ( Figure 5) (14). In our initial studies we found that EncFtn-W38A was not amenable to native mass spectrometry analysis due to poor solubility in native MS ammonium acetate buffer; consequently, native MS was performed on EncFtn-WT, EncFtn-E31A, EncFtn-E34A, and EncFtn-W38G.…”
Section: Native Mass Spectrometry Reveals Conformational Heterogeneitmentioning
confidence: 99%
See 3 more Smart Citations